Bad guys: why the public supports punishing white-collar offenders - Cullen, Francis T. (Crime, law and social change, 2009)
Until the latter part of the 1960s, the American public was inattentive to the problem of crime in the upperworld. Due to a confluence of events (e.g., Watergate affair, Vietnam War, civil rights movement), concern about this lawlessness rose precipitously in the 1970s. Public attention toward and willingness to punish white-collar crime has persisted into the twenty-first century. We argue, however, that due to a series of recent scandals (e.g., Enron, WorldCom), public opinion about upperworld offenders has been transformed qualitatively. High-profile offenders are now seen not as respected community citizens but as "bad guys" whose crimes reflect inordinate greed and a disturbing lack of concern for victims. This typification is conducive to the prosecution of white-collar offenders but may have the unanticipated consequence of deflecting attention away from structural sources of corporate illegal enterprises.